Conceptualizing Consumer Acceptance of Innovations - Butcher, Luke Kevin (Curtin University, 2015)
Addressing the limited understanding of what drives a consumer to break from their current consumption status quo and accept a new product innovation, this research successfully develops an extensive theoretical framework comprising of cognitive and effective measures of familiarity, attitude, compatibility, and enablers. This model of consumer innovation acceptance is proven suitable across levels of mild and high innovativeness (as perceived by the consumer), and is further validated through comparisons with a non-innovative control sample.